An assessment of the impact of Koshi floods to birds and mammals - Baral, Hem Sagar (Nepalese Journal of Biosciences, 2013)
Flood impact assessment with a focus on wetland dependent birds and mammals was carried out in 2009. Data compared to 2008, showed decline in the total number of birds. The results showed that while some bird benefitted from replenished fish stock, many others suffered. South Asian River Dolphin Platanista gangetica increased in number within the Koshi Tappu Wildlife Reserve after the flooding. Poverty and illiteracy contributing to lack of awareness amongst local people were hampering conservation works in the Reserve. DOI: http://dx.doi.org/10.3126/njbs.v2i0.7482 Nepalese Journal of Biosciences 2 : 1-4 (2012)